A fresh pH-responsive imipenem-loaded nanocarrier against Acinetobacter baumannii with a synergetic effect - Gui, Shumin; Li, Xisheng; Feng, Mingming; Liu, Hui; Huang, Liwenhui; Niu, Xinqing (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, the treatment of Acinetobacter baumannii infections has become a pressing clinical challenge due to its increasing incidence and its serious pathogenic risk. The research and development of new antibacterial agents for Acinetobacter baumannii have attracted the attention of the scientific community. Therefore, we have constructed a new pH-responsive antibacterial nano-delivery system (Imi@ZIF-8) for the antibacterial treatment of Acinetobacter baumannii. Due to its pH-sensitive characteristics, the nano-delivery system offers an improved release of the loaded imipenem antibiotic at the acidic infection site. Based on the high loading capacity and positive charge of the modified ZIF-8 nanoparticles, they are excellent carriers and are suitable for imipenem loading. The Imi@ZIF-8 nanosystem features synergistic antibacterial effects, combining ZIF-8 and imipenem to eliminate A. baumannii through different antibacterial mechanisms. When the loaded imipenem concentration reaches 20ug/ml, Imi@ZIF-8 is highly effective against Acinetobacter baumannii in vitro. Imi@ZIF-8 not only inhibits the biofilm formation of A. baumannii but also has a potent killing effect. Furthermore, in mice with celiac disease, the Imi@ZIF-8 nanosystem demonstrates excellent therapeutic efficacy against A. baumannii at imipenem concentrations of 10 mg/kg, and it can inhibit inflammatory reaction and local leukocyte infiltration. Due to its biocompatibility and biosafety, this nano-delivery system is a promising therapeutic strategy in the clinical treatment of A. baumannii infections, providing a new direction for the treatment of antibacterial infections.